THE EFFECT OF FILLING THE GAS PIPELINE WITH CONDENSATE ON TRANSPORT PRESSURE - Elman Iskandarov; Fidan Ismayilova; Mahammad Shukurlu; Anar Nagizadeh (Rudarsko-geološko-naftni Zbornik, 2025)
The analysis of the transportation of natural gases and associated petroleum gases indicates that, unlike natural gases, it is impossible to transport associated gases over long distances as a monophase state. In some cases, associated petroleum gas is injected into the reservoir to enhance oil recovery through gas lift operations. However, the specific demand for gas at production facilities is much lower compared to available gas resources. On the other hand, modern concepts regarding the use of natural gases and associated gases require that they are prepared and transported to the consumer in accordance with regulatory standards. The increased demand in export gas has made it necessary to collect, prepare, and transport the associated gases produced alongside oil without losses through pipelines to the destination. Compared to dry gases, the collection and transportation of associated petroleum gases involve several technological challenges. During these processes, the pipeline may fill with condensate due to the condensation of the associated gas. This situation requires the calculation of gas condensation along the pipeline route. This paper investigates the change in transportation pressure in the gas pipeline depending on the degree of pipeline filling with condensate at various gas flow rates. It has been found that during the multiphase flow of associated gas, an increase in pressure is observed due to the accumulation of condensate in the gas pipeline.